2003
DOI: 10.1007/s00535-003-1158-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastric electrical activity in normal neonates during the first year of life: effect of feeding with breast milk and formula

Abstract: An adult-like gastric 3-cpm activity can be observed in breast-fed newborns in contrast to formula-fed ones, probably as an effect of colostrum. The high bradygastria percentage recorded at 6 months of life might be the result of an increased low-frequency component of the EGG signal because of the transition to a mixed diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
4
18
3
Order By: Relevance
“…Recently, it has been demonstrated that breast-fed infants display an adult-like gastric activity in contrast to formula-fed ones [9]. However, we did not find any differences in the observed parameters between the 2 groups, but it can be explained by the small number of the patients.…”
Section: Resultscontrasting
confidence: 52%
“…Recently, it has been demonstrated that breast-fed infants display an adult-like gastric activity in contrast to formula-fed ones [9]. However, we did not find any differences in the observed parameters between the 2 groups, but it can be explained by the small number of the patients.…”
Section: Resultscontrasting
confidence: 52%
“…The gastric electrical activity in healthy full-term newborns fed with formula or breast-milk was compared during the first 6 months of life [139]. An adult-like gastric 3 cpm activity can be observed in breast-fed newborns in contrast to formula-fed ones, probably as an effect of colostrum.…”
Section: Clinical Significance Of Eggmentioning
confidence: 99%
“…It is often stated that gastric emptying is slower in neonates, especially premature ones, compared with older infants and children 14, 15, 16, 17, 18, 19. This is usually assigned to immaturity of the neuro‐regulation of motility, although data on the postnatal development of gastric motility are equivocal.…”
Section: Introductionmentioning
confidence: 99%